Pembelajaran Online yang Efektif di Masa Pandemi Covid-19 Studi Kasus di SMP Negeri 4 Pakem Sleman - Murhadi Murhadi; Ponidi Ponidi (INTEK : Jurnal Informatika dan Teknologi Informasi, 2020)
Schools as places of interaction between teachers and students must limit interactions due to the Covid-19 pandemic. The government issued an instruction to oblige the implementation of learning from each home. SMP Negeri 4 Pakem implements online learning as an effective learning effort in the era of the Covid-19 outbreak. This article was prepared based on the implementation of online learning at SMP Negeri 4 Pakem. This article is a documentation of the process of designing, implementing, and evaluating the implementation of teaching-learning. Data is collected from the entire process of implementing online learning so that its effectiveness can be seen to replace the regular learning process. The implementation of online learning conducted at SMP Negeri 4 Pakem in the era of the Covid-19 outbreak was running effectively. The learning planning process is carried out by compiling a learning schedule that is different from regular learning. Online learning is carried out using many online platforms. The distribution of information on the learning process to students is done through the WhatsApp group. Learning is carried out through Google Classroom, for learning management and for face to face using video conferencing. The online evaluation and test processes are carried out using Google Form. The online learning evaluation process involves students and parents. From the results of the evaluation carried out, online learning does not burden students because its implementation is directly monitored by the school principal, and by using very clear signs.